(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1852)
Thomas Brown exhibited a stone mould that was used for casting weapons and other tools. It was made of green serpentine, oval in shape, and 16.5"L x 9.5"W x 2.25"H in dimension. The woodcut which accompanies the article illustrates the front of the mould, including a long hollow, which Brown believed was used to get the rough shape of a dagger blade.